Body mass index and risk of recurrent falls in community‐dwelling Japanese aged 40–74 years: The Murakami cohort study. Issue 6 (21st April 2021) - Nakamura, Kazutoshi; Kitamura, Kaori; Watanabe, Yumi; Kabasawa, Keiko; Takahashi, Akemi; Hinata, Aya; Saito, Toshiko; Kobayashi, Ryosaku; Oshiki, Rieko; Takachi, Ribeka; Tsugane, Shoichiro; Iki, Masayuki; et al.
Abstract : Aims: A prior meta‐analysis found that obesity (body mass index [BMI] ≥ 30 kg/m 2 ) was associated with a high fall risk, while being overweight (BMI≥25, <30 kg/m 2 ) was associated with the lowest fall risk. However, whether these associations hold true for East Asians is unknown. This study aimed to assess the association between BMI and incidence of recurrent falls in Japanese aged 40–74 years. Methods: This 5‐year follow‐up cohort study involved 7538 community‐dwelling individuals who did not experience recurrent falls in the year before the baseline study. Information on demographics, body size, lifestyle, and disease history was obtained using a self‐administered questionnaire. BMI was categorized as <18.5 (underweight), 18.5–20.6 (low‐normal), 20.7–22.7 (mid‐normal, reference), 22.8–24.9 (high‐normal), and ≥ 25.0 kg/m 2 (overweight). The outcome was recurrent falls reported, and fall history in the previous year was recorded as none, once, or twice or more (recurrent falls). Results: Mean BMI was 23.5 kg/m 2 (SD 2.9) for men and 22.7 kg/m 2 (SD 3.2) for women. The adjusted odds ratio (OR) for recurrent falls in the BMI ≥25 group was significantly higher (1.41, 95%CI: 1.02–1.93) than that in the reference group. The adjusted OR in the BMI ≥25 group was significantly higher than that in the reference group for the age ≥ 60 subgroup (1.62, 95%CI: 1.09–2.40), but not for the age < 60 subgroup (OR = 1.04, 95%CI: 0.60–1.80). Conclusions: Being overweight may be a risk factor for recurrent falls in community‐dwelling older Japanese. Further studies are needed to determine the underlying mechanism. Geriatr Gerontol Int 2021; 21: 498–505 .